Carbon / silicon / graphite composite negative electrode material, preparation method and application

By using carbon/silicon/modified worm graphite composite negative electrode material, the problem of low discharge capacity of the existing sodium ion battery hard carbon negative material is solved. The energy density and service life of the battery.

CN119361635APending Publication Date: 2025-01-24EAST CHINA UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411469803.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The discharge capacity of the hard carbon anode material of existing sodium ion batteries is lower at a current density of 100mA/g, which is lower than that of the graphite anode material of lithium ion batteries, resulting in the energy density of sodium ion batteries being lower than that of existing commercial lithium ion batteries.

Method used

A composite negative electrode material composed of a carbon layer, a nano-silicon layer and a modified worm graphite layer is used. The nano-silicon layer is formed by chemical vapor deposition, and the modified worm graphite is heat treated at high temperature to form a composite material with high conductivity.

Benefits of technology

It improves the discharge capacity and charge and discharge speed of the sodium-ion battery anode material, increases the energy density of the sodium-ion battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a carbon / silicon / graphite composite negative electrode material, a preparation method and application, and relates to the technical field of negative electrode materials. Comprising the following steps that S1, a silicon source forms a nanometer silicon layer on the surface of a graphite layer through a chemical vapor deposition method, a silicon / graphite composite material is obtained, and the graphite layer is formed after worm graphite is subjected to high-temperature heat treatment modification; s2, dipping the silicon / graphite composite material in a solution of a carbon-rich precursor; s3, in an inert gas environment, performing hot press molding on the impregnated silicon / graphite composite material to prepare a sheet; s4, performing high-temperature carbonization treatment on the sheet in a nitrogen environment and a normal-pressure state; and S5, preparing the carbonized sheets into micron particles. The material has the advantages of good conductivity, good discharge capacity, good cycle stability, capability of improving the charge-discharge speed of the sodium ion battery and the like, and has wide application potential and application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials, and in particular relates to a carbon / silicon / graphite composite negative electrode material, a preparation method and an application thereof. Background Art

[0002] The high energy density of lithium-ion batteries has led to their widespread practical application in transportation, electronics, machinery, and power storage for wind and solar power generation. Since the abundance of metallic lithium on Earth is much lower than that of metallic sodium, the increasing depletion of lithium resources will inevitably affect the long-term large-scale application of lithium-ion batteries.

[0003] The charging and discharging principle of sodium-ion batteries is similar to that of lithium-ion batteries, that is, the electrochemical reaction process of lithium or sodium ions embedding and extracting between the positive and negative electrodes. In terms of electrochemical performance, sodium-ion batteries have better low-temperature electrochemical performance, higher safety and longer cycle stability in addition to higher energy density.

[0004] At the same time, the preparation process of the positive / negative electrodes, battery assembly process, and components such as the shell and tabs of sodium-ion batteries and lithium-ion batteries are the same. In other words, the mature existing industrial processes and equipment of lithium-ion batteries have laid a good industrial foundation for the rapid development of sodium-ion batteries. Therefore, sodium-ion batteries are regarded as the most promising new type of secondary batteries after lithium-ion batteries and have received widespread attention.

[0005] Since the kinetic diameter of sodium ions is larger than that of lithium ions, the existing graphite negative electrode materials of lithium ion batteries are not suitable for use as negative electrode materials for sodium ion batteries. Therefore, it is urgent to develop a new generation of negative electrode materials for sodium ion batteries.

[0006] At present, Chinese patents 202410465536.4, 202410238556.8, 202410377318.5, 201510346139.6, 202310493118.1, 202310765031.5, and 202410432731.7 respectively disclose negative electrode materials for sodium ion batteries using biomass such as coal, asphalt, synthetic resin, corn leaves, coconut shells, fruit shells, and bamboo charcoal as carbonaceous precursors, which are activated by water vapor or carbon dioxide and carbonized at high temperature, namely hard carbon negative electrode materials.

[0007] However, the hard carbon negative electrode material of the sodium ion battery prepared by this preparation method generally has a discharge capacity of only 200-280mAh / g at a current density of 100mA / g, which is correspondingly lower than the graphite negative electrode material of the lithium ion battery. Generally, the theoretical capacity of the graphite negative electrode material of the lithium ion battery is 372mAh / g, and the actual capacity can reach 320mAh / g, so the energy density of the sodium ion battery is lower than that of the existing commercial lithium ion battery.

[0008] In summary, how to provide a negative electrode material with higher discharge capacity suitable for sodium ion batteries is a technical problem that urgently needs to be solved. Summary of the invention

[0009] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a carbon / silicon / graphite composite negative electrode material, a preparation method and an application thereof, which improve the conductivity of the negative electrode material, can increase the discharge capacity of the negative electrode material of a sodium ion battery, and thus improve the energy density of the sodium ion battery.

[0010] The present invention provides a carbon / silicon / graphite composite negative electrode material. The composite negative electrode material is a micron particle composed of a carbon layer, a nano silicon layer and a graphite layer stacked in sequence from top to bottom. The graphite layer is formed by modifying worm graphite through high temperature heat treatment.

[0011] Furthermore, the specific surface area of ​​the composite negative electrode material is 5-20 m 2 / g, and the average particle size is 5-15μm.

[0012] Furthermore, the content of nano-silicon in the composite negative electrode material is 5-30%.

[0013] Furthermore, the thickness of the carbon layer is 0.1-0.5 nm; the thickness of the nano-silicon layer is 0.5-1.5 nm.

[0014] Furthermore, the carbon layer is formed on the surface of the nano-silicon layer by cracking of the carbonized silicon / graphite composite sheet under high-temperature carbonization treatment.

[0015] The present invention provides a method for preparing the carbon / silicon / graphite composite negative electrode material as described in any one of the above, comprising the following steps: S1: forming a nano-silicon layer on the surface of the graphite layer by chemical vapor deposition of a silicon source to obtain a silicon / graphite composite material, wherein the graphite layer is formed after the worm graphite is modified by high-temperature heat treatment; S2 immerses the silicon / graphite composite material in a solution of a carbon-rich precursor; S3, in an inert gas environment, forming the impregnated silicon / graphite composite material into a sheet by hot pressing; S4 performs high temperature carbonization treatment on the sheet in a nitrogen environment and normal pressure; S5 prepares the carbonized sheets into micron particles.

[0016] Further, the silicon source is selected from silane; The deposition temperature of the chemical vapor deposition method described in S1 is 500-600° C., the flow rate of the dilution gas is 10-200 ml / min; and the deposition time is 30-120 min.

[0017] Furthermore, the carbon-rich precursor in S2 is any one of ethylene tar, naphtha, coal tar, or a mixture of two or more thereof.

[0018] Further, the hot pressing molding in S3 includes using the heavy component generated during the hot pressing molding of the aforementioned carbon-rich precursor as a binder; The hot pressing temperature of the hot pressing molding is 300-400° C., and the molding pressure is 5-20 MPa.

[0019] Furthermore, the heat treatment temperature of the high temperature heat treatment process in S4 is 700-1500° C., and the heat treatment time is 60-240 min.

[0020] The present invention provides a sodium ion battery, comprising a negative electrode made of a negative electrode material prepared by any one of the methods described above.

[0021] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art, as an example: By using high-temperature modified worm graphite, the oxygen-containing functional groups on the graphite surface are decomposed. The graphite molecular structure provides a pathway for electron migration during the charging and discharging process, thereby improving the electrical conductivity of the material and the charging and discharging speed. The carbon layer on the surface of the composite material also enhances the wettability with the electrolyte, further improving the charging and discharging speed.

[0022] The combination of carbon / Si / graphite effectively solves the problems of low conductivity and volume expansion of single nano-Si, enhances the cycle stability and prolongs the battery life.

[0023] In addition, by reducing the specific surface area of ​​the material, it helps to reduce the use of organic electrolyte, reduce costs and reduce environmental impact.

[0024] This composite negative electrode material exhibits high discharge capacity, fast charge and discharge speed, excellent conductivity and good cycle stability. It has broad application potential and can promote the rapid development of sodium-ion batteries in energy storage, electronic products, transportation and machinery. DETAILED DESCRIPTION

[0025] The technical solution disclosed in the present invention is described in detail below in conjunction with specific embodiments.

[0026] The techniques and preparation methods known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the techniques and preparation methods should be considered as part of the specification. In all examples shown and discussed herein, any specific value should be interpreted as merely exemplary and not as a limitation. Therefore, other examples of the exemplary embodiments may have different values.

[0027] The invention provides a method for preparing a carbon / silicon / graphite composite negative electrode material.

[0028] S1 forms a nano-silicon layer on the surface of the graphite layer by chemical vapor deposition of silicon source to obtain a silicon / graphite composite material.

[0029] In this embodiment, by way of example and not limitation, the graphite is commercial worm graphite that is modified by a high temperature heat treatment at 300-1500°C.

[0030] The reason for choosing worm graphite as raw material is, on the one hand, to utilize the unique graphite interlayer structure of worm graphite to provide a place for the subsequent deposition of nano-Si; on the other hand, to utilize the graphite molecular structure of worm graphite after high-temperature heat treatment to provide a path for electron migration during the charging and discharging process.

[0031] The silicon source is selected from silane.

[0032] The deposition temperature of the chemical vapor deposition method described in S1 is 500-600° C., the flow rate of the dilution gas is 10-200 ml / min; and the deposition time is 30-120 min.

[0033] S2 immerses the silicon / graphite composite material in a solution of a carbon-rich precursor.

[0034] The carbon-rich precursor solution in S2 is any one of ethylene tar, naphtha, coal tar, or a mixture of two or more thereof.

[0035] S3 forms a sheet by hot pressing the impregnated silicon / graphite composite material under an inert gas environment.

[0036] The hot pressing temperature of the hot pressing molding is 300-400° C., and the molding pressure is 5-20 MPa.

[0037] The hot pressing molding here does not add any additional binder, but directly uses the recombinant component generated during the hot pressing molding process of the carbon-rich precursor solution on the silicon / graphite composite material as the binder.

[0038] By way of example and not limitation, the heavy components include organic compounds having 3-10 benzene rings.

[0039] S4 performs high temperature carbonization treatment on the sheet in a nitrogen environment and normal pressure.

[0040] The heat treatment temperature is 700-1500°C, and the heat treatment time is 60-240min.

[0041] During the high-temperature heat treatment process at 700-1500℃, the oxygen-containing functional groups on the surface of the worm graphite will decompose, making the negative electrode material have a higher conductivity, which is beneficial to improving the charging and discharging speed of the sodium-ion battery.

[0042] By hot pressing in S3 and high temperature heat treatment in S4, the specific surface area of ​​the obtained carbon / Si / graphite composite negative electrode material can be reduced, for example but not by limitation, to less than 20 m 2 / g, thereby effectively reducing the amount of organic electrolyte used.

[0043] S5 forms the carbonized sheet into micron particles.

[0044] The following steps are usually involved: The carbonized sheets are made into granular particles with a particle size of 1-3 mm by mechanical crushing.

[0045] Then, a mechanical ball milling device is used to ball mill the millimeter-sized particles into micron-sized particles with a particle size of 5-15 μm, which is the carbon / Si / graphite composite negative electrode material provided by the present invention.

[0046] The present invention provides a carbon / silicon / graphite composite negative electrode material prepared by the above method, which is a micron particle composed of a carbon layer, a nano silicon layer and a graphite layer stacked in sequence from top to bottom.

[0047] The nano silicon layer is grown on the surface of the graphite layer by chemical vapor deposition, and the carbon layer is formed on the surface of the nano silicon layer by cracking the carbonized silicon / graphite composite sheet under high temperature carbonization treatment.

[0048] The formation of a carbon layer on the surface of the nano-Si layer is beneficial to improving the wettability of the negative electrode material with the organic electrolyte, thereby increasing the charge and discharge speed of the sodium ion battery.

[0049] The superimposed structure of carbon / Si / graphite can compensate for the defects of single nano-Si such as low conductivity and insufficient volume expansion during the charge and discharge process, so that the composite negative electrode material has better long-cycle stability.

[0050] The carbon / silicon / graphite composite negative electrode material generally has the following characteristics: Specific surface area is 5-20 m 2 / g, and the average particle size is 5-15μm.

[0051] The content of nano silicon is 5-30%.

[0052] The thickness of the carbon layer is 0.1-0.5 nm; the thickness of the nano silicon layer is 0.5-1.5 nm.

[0053] The specific preparation process and results of the present invention are as follows:

[0054] Example 1 10g of commercial worm graphite was placed in a quartz tube of a chemical vapor deposition furnace, silane was used as the silicon source, and the flow rate of silane gas was 50ml / min; argon was used as the inert gas, and the flow rate of argon gas was 100ml / min; the deposition temperature was 550℃, and the deposition time was 80min to obtain a silicon / graphite composite material.

[0055] 100 ml of ethylene tar was placed in 400 ml of ethanol solvent and stirred at room temperature for 30 minutes. Then 5 g of the prepared material was placed in 500 ml of ethylene tar / ethanol solution and immersed at room temperature for 60 minutes. The solid phase components were collected by filtration and dried at 150°C for 120 minutes under nitrogen protection to remove trace light components in ethanol and ethylene tar.

[0056] 5g of the dried sample was placed in a hot pressing molding device, and the temperature was raised to 350°C at 10°C / min in an argon atmosphere, and the temperature was kept constant for 120 minutes. At the same time, a molding pressure of 10MPa was applied to make the dried sample into a 1mm thick sheet. The prepared sheet was placed in a high-temperature furnace and kept constant at 850°C in a nitrogen protective atmosphere for 120 minutes. The sheet after high-temperature heat treatment was crushed into granular particles with a particle size of about 1mm by a mechanical crushing method. Finally, a mechanical ball milling device was used to ball-mill the granular particles into micron-sized particles with a particle size of 5-15μm, thereby obtaining a carbon / Si / graphite composite negative electrode material for sodium ion batteries.

[0057] Among them, the specific surface area of ​​the prepared carbon / Si / graphite composite negative electrode material is 15.3m 2 / g, and an average particle size of 5-15μm; the content of the nano-Si in the composite negative electrode material is 11.6%, the thickness of the nano-Si layer grown on the surface of the graphite layer is 1.2nm, and the thickness of the carbon layer on the surface of the nano-Si layer is 0.3nm.

[0058] When the carbon / Si / graphite composite material prepared under the conditions of this embodiment is used as the negative electrode material of a sodium ion battery, the first discharge capacity is as high as 871 mAh / g at a current density of 100 mA / g, and the discharge is maintained at 412 mAh / g after repeated charge and discharge for 200 times.

[0059] Example 2 The hot pressing conditions in [Example 1] were adjusted to: hot pressing temperature of 380°C, molding pressure of 15 MPa. All other preparation conditions were the same as [Example 1].

[0060] The specific surface area of ​​the prepared carbon / Si / graphite composite negative electrode material is 12.2 m 2 / g, and an average particle size of 5-15μm; the content of the nano-Si in the composite negative electrode material is 11.8%, the thickness of the nano-Si layer grown on the surface of the graphite layer is 1.2nm, and the thickness of the carbon layer on the surface of the nano-Si layer is 0.3nm.

[0061] When the carbon / Si / graphite composite material prepared under the conditions of this embodiment is used as the negative electrode material of a sodium ion battery, the first discharge capacity is as high as 875 mAh / g at a current density of 100 mA / g, and the discharge capacity can still be maintained at 571 mAh / g after repeated charge and discharge for 200 times.

[0062] Example 3 The hot pressing conditions in [Example 1] were adjusted to: hot pressing temperature 380° C., molding pressure 15 MPa. At the same time, the heat treatment temperature of the prepared sheet was increased to 1500° C. All other preparation conditions were the same as [Example 1].

[0063] The specific surface area of ​​the prepared carbon / Si / graphite composite negative electrode material is 9.8m 2 / g, with an average particle size of 5-15μm; the content of the nano-Si in the composite negative electrode material is 12.1%. However, due to the high carbonization temperature, the nano-Si layer grown on the surface of the graphite layer during the chemical vapor deposition process will react with the matrix carbon during the high-temperature carbonization process of 1500°C to form a SiC layer with a thickness of 1.2nm, and the thickness of the carbon layer on the surface of the nano-SiC layer is 0.25nm.

[0064] When the carbon / SiC / graphite composite material prepared under the conditions of this embodiment is used as the negative electrode material of a sodium ion battery, the initial discharge capacity is only 175 mAh / g at a current density of 100 mA / g, and the discharge is maintained at 117 mAh / g after repeated charge and discharge for 200 times.

[0065] Example 4 The ethylene tar in [Example 1] was replaced with naphtha; at the same time, the hot pressing molding conditions were adjusted to: hot pressing temperature of 380°C, molding pressure of 15 MPa. All other preparation conditions were the same as [Example 1].

[0066] The specific surface area of ​​the prepared carbon / Si / graphite composite negative electrode material is 12.9 m 2 / g, and an average particle size of 5-15μm; the content of the nano-Si in the composite negative electrode material is 12.3%, the thickness of the nano-Si layer grown on the surface of the graphite layer is 1.2nm, and the thickness of the carbon layer on the surface of the nano-Si layer is 0.1nm.

[0067] When the carbon / Si / graphite composite material prepared under the conditions of this embodiment is used as the negative electrode material of a sodium ion battery, the first discharge capacity is as high as 877 mAh / g at a current density of 100 mA / g, and the discharge capacity can still be maintained at 581 mAh / g after repeated charge and discharge for 200 times.

[0068] In summary, the carbon / Si / graphite composite negative electrode material for sodium ion batteries obtained by the preparation method provided by the present invention has a discharge capacity of 500-600mAh / g after 200 cycles at a current density of 100mA / g, which is 2-3 times the general discharge capacity of the current hard carbon negative electrode material for sodium ion batteries.

[0069] In the scope of the intended protection of the present disclosure, terms such as "including" and the like should be interpreted as inclusive or open by default, rather than exclusive or closed, unless they are expressly defined to the contrary. All technical, scientific or other terms have the meanings understood by those skilled in the art unless they are defined to the contrary. Common terms found in dictionaries should not be interpreted too idealistically or too impractically in the context of relevant technical documents, unless the present disclosure expressly defines them as such.

[0070] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0071] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A carbon / silicon / graphite composite negative electrode material, characterized in that: The composite negative electrode material is a micron particle composed of a carbon layer, a nano silicon layer and a graphite layer stacked in sequence from top to bottom; the graphite layer is formed by modifying worm graphite through high-temperature heat treatment.

2. The carbon / silicon / graphite composite negative electrode material according to claim 1, characterized in that: The specific surface area of ​​the composite negative electrode material is 5-20 m 2 / g, and an average particle size of 5-15μm; the content of nano-silicon in the composite negative electrode material is 5-30%.

3. The carbon / silicon / graphite composite negative electrode material according to claim 1, characterized in that: The thickness of the carbon layer is 0.1-0.5 nm; the thickness of the nano silicon layer is 0.5-1.5 nm.

4. The carbon / silicon / graphite composite negative electrode material according to claim 1, characterized in that: The carbon layer is formed on the surface of the nano silicon layer by cracking the carbonized silicon / graphite composite sheet under high temperature carbonization treatment.

5. A method for preparing the carbon / silicon / graphite composite negative electrode material as described in any one of claims 1 to 4, characterized in that: The steps include: S1: forming a nano-silicon layer on the surface of the graphite layer by chemical vapor deposition of a silicon source to obtain a silicon / graphite composite material, wherein the graphite layer is formed after the worm graphite is modified by high-temperature heat treatment; S2 immerses the silicon / graphite composite material in a solution of a carbon-rich precursor; S3, in an inert gas environment, forming the impregnated silicon / graphite composite material into a sheet by hot pressing; S4 performs high temperature carbonization treatment on the sheet in a nitrogen environment and normal pressure; S5 The carbonized sheets are made into micron particles.

6. The method according to claim 5, characterized in that: The graphite layer in S1 is graphite formed after worm graphite is modified by high-temperature heat treatment; The silicon source is selected from silane; The deposition temperature of the chemical vapor deposition method described in S1 is 500-600° C., the flow rate of the dilution gas is 10-200 ml / min; and the deposition time is 30-120 min.

7. The method according to claim 5, characterized in that: The carbon-rich precursor in S2 is any one of ethylene tar, naphtha, coal tar, or a mixture of two or more thereof.

8. The method according to claim 5, characterized in that: The hot pressing molding in S3 includes using the heavy component generated during the hot pressing molding of the aforementioned carbon-rich precursor as a binder; The hot pressing temperature of the hot pressing molding is 300-400° C., and the molding pressure is 5-20 MPa.

9. The method according to claim 5, characterized in that: The heat treatment temperature of the high temperature heat treatment process in S4 is 700-1500° C., and the heat treatment time is 60-240 min.

10. A sodium ion battery comprising a negative electrode made of the negative electrode material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for preparing sodium-ion battery electrode carbon material from corn leaves

    CN105036108A

  • Preparation method of coconut shell-based hard carbon material and sodium ion battery

    CN116553514A

  • Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material

    CN117133886A

  • Sodium-ion battery bamboo charcoal composite negative electrode and preparation method thereof

    CN118039884A

  • Asphalt-based hard carbon material for negative electrode of sodium ion battery and preparation method of asphalt-based hard carbon material

    CN118239467A